2018
DOI: 10.1212/cpj.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

Wake-up stroke is not associated with sleep-disordered breathing in women

Abstract: In this population-based study, WUS represented about 30% of all generally mild severity ischemic strokes in women and was not associated with SDB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…In our previous study, higher proportion of males had OSA. In a study by Brown et al (2018) they did not find a relationship between female, SDB, and mild WUS (Brown et al, 2018).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In our previous study, higher proportion of males had OSA. In a study by Brown et al (2018) they did not find a relationship between female, SDB, and mild WUS (Brown et al, 2018).…”
Section: Discussionmentioning
confidence: 83%
“…In a study by Brown et al. (2018) they did not find a relationship between female, SDB, and mild WUS (Brown et al., 2018).…”
Section: Discussionmentioning
confidence: 96%
“…The cross-sectional analysis of data from the Sleep Apnea in Transient Ischemic Attack and Stroke (SLEEP TIGHT) study has also shown in 81 stroke patients who underwent polysomnography in the subacute phase (median interval from stroke: 48 days) that patients with WUS had 12 significantly higher rates of severe OSA but this difference was only significant for men (AHI>30: 45.0% vs. 17.6%; p=0.03) [74]. Such a difference in sex was recently confirmed by Brown et al in 259 women with acute ischemic stroke who benefited from apnea screening using the ApneaLink Plus device (AL; Resmed, Poway, CA, USA) a median 11 days poststroke: WUS was not associated with the presence or severity of OSA in unadjusted or adjusted analysis (prevalence of respiratory event index ≥10/h: 55.4% in WUS vs 52.4% in non-WUS women) [75].…”
Section: Osa Is a Risk Factor Of Strokementioning
confidence: 78%
“…A recent prospective study has found an independent association between newly diagnosed atrial fibrillation (AF) and WUS; the odds of detecting a newly diagnosed AF were 3-fold higher among wake-up cerebrovascular events than among non-wake-up events [24]. In this prospective study including 356 patients (274 stroke and 82 transient ischemic attack, median age 72 years (interquartile range, IQR [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]), AF was detected with immediate and continuous electrocardiographic monitoring for at least 72 hours after admission: 41 (11.5%) events occurred during night sleep. Among WUS patients, 17.1% were newly diagnosed with AF (vs. 6.3% of non-WUS patients, p=0.015), and the association remained significant after adjusting for age, sex, hypertension, severity of neurological deficit on admission, left ventricular fraction, atrial area, and diabetes mellitus [24].…”
Section: Circadian Factormentioning
confidence: 99%
“…A population-based prospective study of WUS in women enrolled 466 participants; of whom, 25% reported that strokes began during nocturnal sleep in 25%, during a nap in 4%, awake in 66%, and unknown in 5%. 18 Sleep apnea testing was performed a median of 11 days (IQR 5, 17) after stroke onset. Sleep disordered breathing (SDB) was not associated with WUS in unadjusted or adjusted analysis.…”
Section: What Predisposes To Stroke In Sleep?mentioning
confidence: 99%